An alternative method for determining the coefficient of thermal expansion of composite material of spherical particles - Duc, Nguyen Dinh; Tung, Hoang Van; Hang, Do Thanh (Vietnam Journal of Mechanics, 2007)
Composite material is widely used in modern structures. Many researchers have been involved in studying, developing and applying this kind of material. The composite material of spherical particles is a material composed of continuous matrix phase and spherical particles. In modern technique, it is very necessary to consider the influence of temperature on toughness and stability of structures. Therefore, determining the coefficient of thermal expansion of composite as a function of the coefficients and volume fractions of matrix and particle phases is a practical requirement. In this paper. we would like to introduce an alternative derivation method in order to obtain the thermal expansion coefficient of two-phase composite of spherical particles. Our results are the same as Vanin’s and other authors’.